Full panorama images of 56 field plot centres during the expedition to Chukotka and Yakutia, summer 2018 - Stefan Kruse; Luca Farkas (PANGAEA, 2025)
During an expedition to central and eastern Siberia in summer 2018, full panoramic images of the sampled vegetation plots were captured for documentation purposes. The images were taken with a 360 camera (Samsung Gear 360) and from the centre 2-4 images recorded at the centre position of the vegetation plot standing at different positions. The images were stitched in the supplied software to 360x180 panorama images (7776x3888 pixels, raw images). These were aligned in Hugin Panorama Software (https://hugin.sourceforge.io/) and humans or other artificial objects masked. The final panorama was blended and gaps or human shadow errors healed with GIMP resynthesizer plugin (https://github.com/bootchk/resynthesizer) and exported into one image with 7776x3888 pixels.